Komputasi Aliran Daya Optimal Sistem Tenaga Skala Besar dengan Metode Primal Dual Interior Point - Syafii Syafii; Ikhwannul Kadri Masrul (Jurnal Rekayasa Elektrika, 2016)
This paper focuses on the use of Primal Dual Interior Point method in the analysis of optimal power flow. Optimal power flow analysis with Primal Dual Interior Point method then compared with Linear Programming Method using Matpower program. The simulation results show that the computation results of Primal Dual Interior Point similar with Linear Programming Method for total cost of generation and large power generated by each power plant. But in terms of computation time Primal Dual Interior Point method is faster than the method of Linear Programming, especially for large systems. Primal Dual Interior Point method have solved the problem in 40.59 seconds, while Linear Programming method takes longer 239.72 seconds for large-scale system 9241 bus. This is because the settlement PDIP algorithm starts from the starting point x0, which is located within the area of feasible move towards the optimal point, in contrast to the simplex method that moves along the border of the feasible from one extreme point to the other extreme point. Thus Primal Dual Interior Point method have more efficient in solving optimal power flow problem of large-scale power systems.